Moyamoya Disease With Initial Ischemic or Hemorrhagic Attack Shows Different Brain Structural and Functional Features: A Pilot Study - Hu, Junwen; Li, Yin; Tong, Yun; Li, Zhaoqing; Chen, Jingyin; Cao, Yang; Zhang, Yifan; Xu, Duo; Zheng, Leilei; Bai, Ruiliang; Wang, Lin (Frontiers in Neurology, 2022)
Objective Cerebral ischemia and intracranial hemorrhage are the two main phenotypes of moyamoya disease (MMD). However, the pathophysiological processes of these two MMD phenotypes are still largely unknown. Here, we aimed to use multimodal neuroimaging techniques to explore the brain structural and functional differences between the two MMD subtypes. Methods We included 12 patients with ischemic MMD, 10 patients with hemorrhagic MMD, and 10 healthy controls (HCs). Each patient underwent MRI scans and cognitive assessment. The cortical thickness of two MMD subtypes and HC group were compared. Arterial spin labeling (ASL) and diffusion tensor imaging (DTI) were used to inspect the cerebral blood flow (CBF) of cortical regions and the integrity of related white matter fibers, respectively. Correlation analyses were then performed among the MRI metrics and cognitive function scores. Results We found that only the cortical thickness in the right middle temporal gyrus (MTG) of hemorrhagic MMD was significantly greater than both ischemic MMD and HC (p < 0.05). In addition, the right MTG showed higher ASL-CBF, and its associated fiber tract (arcuate fasciculus, AF) exhibited higher fractional anisotropy (FA) values in hemorrhagic MMD. Furthermore, the cortical thickness of the right MTG was positively correlated with its ASL-CBF values (r = 0.37, p = 0.046) and the FA values of right AF (r = 0.67, p < 0.001). At last, the FA values of right AF were found to be significantly correlated with cognitive performances within patients with MMD. Conclusions Hemorrhagic MMD shows increased cortical thickness on the right MTG in comparison with ischemic MMD and HCs. The increased cortical thickness is associated with the higher CBF values and the increased integrity of the right AF. These findings are important to understand the clinical symptoms and pathophysiology of MMD and further applied to clinical practice.